THE EFFECT OF COLORING PLAY THERAPY ON REDUCING STRESS IMPACT OF HOSPITALIZATION IN PRE-SCHOOL AGE CHILDREN - Dian Herawati; Mariyani Mariyani (Lembaga Pengembangan Kinerja Dosen, 2023)
Background :Hospitalization is a critical condition in children, when the child is sick and is being treated in the hospital. Hospitalization can be considered as a threatening experience and becomes a stressor so that it can cause a crisis for children and families. In an effort to reduce the impact of children from hospitalization experienced by children during child care, we need a medium that can express anxiety, one of which is coloring picture therapy. Data from the Children's Room at Adjidarmo Rangkasbitung hospital found that children who were hospitalized from January to June 2022 had 979 cases of hospitalized children or an average of 163 cases per month. Writing purpose :the effect of giving play therapy coloring pictures on reducing stress due to the impact of hospitalization in pre-school-aged children at Adjidarmo Rangkasbitung Public Hospital, Banten Research methods :This study used a pre-experimental denham design with one group pretest-posttest design. One-group pre-post test design to obtain stress level data before and after the intervention. The number of samples in this study were 32 pre-school children who fit the inclusion criteria. The instrument used for data collection used a questionnaire and then the data were analyzed using the paired t test. Research result :the average stress on children due to hospitalization before the intervention was given was 21.09 pont or included in the moderate category and after the intervention became 13.13 or included in the moderate. There is an effect of giving play therapy coloring pictures to reduce stress due to hospitalization in pre-school-aged children at Adjidarmo Rangkasbitung Hospital, Banten with a p value of 0.000. Conclusions and recommendations:Image coloring play therapy can be effective in reducing stress in children due to hospitalization, therefore health workers can apply image coloring play interventions to children who are hospitalized